Tariff Systems and Distance Measurement of Public Passenger Transport Stops - Gnap, Jozef; Dydkowski, Grzegorz; Ondrus, Jan; Synak, Frantisek (Communications - Scientific Letters of the University of Zilina, 2023)
The development of IT technologies in the systems of tickets sales facilitates the charging and differentiating the fare amounts versus distance, as well as in the systems of public transport on short distances, in the urban, suburban and regional transport. The essence of the transport activity consists in covering a distance and a part of cost components and thereby the total costs, increase with the distance covered by means of transport. In a similar way the calculation of fares depending on distances may be considered as the most appropriate from the point of view of transport as a service. Inaccuracies and deviations during the distance measurements have various results, which further on may have effect on analyses, comparisons, correctness during the fare calculations, as well as settlements related to public financing of the public transport. An independent and precise distance measurement is indispensable to eliminate the impact of the measurement method on distances.
Keywords: public transport; tariff system; measuring; bus-stop distances